Effect of Composition and Processing Conditions on Selected Properties of Potato-Based Pellets and Microwave-Expanded Snacks Supplemented with Fresh Beetroot Pulp - Katarzyna Lisiecka; Agnieszka Wójtowicz; Agnieszka Sujak (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to evaluate the influence of the addition of fresh beetroot pulp in amounts from 2.5 to 30.0 g/100 g, as well as variable screw speeds (60, 80, 100 rpm) on the chemical composition, water absorption, water solubility index, density, expansion rate, and texture of potato-based pellets and expanded snacks. Their protein and starch structure was analyzed using the Fourier-transformed infrared (FTIR) spectroscopy. The snack pellets were made at a moisture content of 33 g/100 g of blends using a single-screw extruder equipped with a plasticizing unit having a length-to-diameter ratio (L/D) of 18. Processing temperature ranged from 65 to 105°C. The ready-to-eat snacks were expanded using microwave treatment (750 W, 40 s). Fresh vegetable pulp addition raised the protein content. The extrusion-cooking caused an increase in the content of insoluble dietary fiber and water absorption index of the pellets. In contrast, the microwave treatment reduced values of these parameters in expanded products and decreased the insoluble dietary fiber content of the expanded snacks. The addition of fresh beetroot pulp diminished the expansion ability and increased the content of β-sheet proteins. Additionally, an increase in the content of β-turn and β-sheet protein fractions was observed at the expense of random coil structure. This indicates that the protein structure underwent some form of ordering as the molecular interactions of the proteins intensified. The highest fraction of β-structures and the smallest content of random coil were observed when 80 rpm was applied during processing. It seems to be the most efficient screw speed in processing fresh beetroot pulp-supplemented snack pellets. Application of a fresh beetroot pulp as an additive in microwave expanded snacks made it possible to obtain products with an increased amount of fiber and a reduced fat content as an attractive and healthy alternative to deep-fried snacks.